Antioxidant Capacity, Total Phenolic, and Flavonoid Content from Java Tea (Orthosiphon aristatus) Extracts - Zulhan Arif; Aurentinus Zalukhu; Alfi Hudatul Karomah; Mohamad Rafi (Tropical Biopharmaca Research Center, IPB University, 2022)
Orthosiphon aristatus, known as kumis kucing in Indonesia, has some biological activity, i.e., as an anti-inflammatory, fever, rheumatism, diabetes, and kidney stone. This plant is also known for being rich in phenolic compounds such as flavonoids. In this study, we would like to compare the antioxidant activity, total phenolics, and flavonoid content from the stems and leaves of Orthosiphon aristatus extracted with water and ethanol by maceration. The yield stem and leaves of the water extract are 12.98-31.28%, and ethanol extract 3.58 - 9.82% (dry basis). The stem and leaves water extract contains a phenolic of 7.82-26.43 (mg GAE/g) and ethanol extract of 2.27-7.84 (mg GAE/g). Water extract Orthosiphon aristatus flavonoid content is 1.23-2.86 (mg EK/g), and ethanol extract is 1.09-3.95 (mg EK/g). The antioxidant activity of ethanol (IC50), extract from leaves was 123.91 (µg/mL) and from stems was 125.50 (µg/mL), while IC50 of water extract from leaves was 114.70 (µg/mL) and from stems was 125.03 (µg/mL). The correlation test result of active compounds using linear regression is phenolic compounds with antioxidants stronger than flavonoids. The qualitative thin-layer chromatography fingerprint analysis showed that ethanol and water extract contained natural sinensetin compounds.